Theoretical Issues for Game-based Virtual Heritage - Champion, Erik (Springer, 2015)
This paper critiques essential features in prominent theories of serious games, and compares them to interaction features of commercial computer games that could be used for history and heritage-based learning in order to develop heuristics that may help future the specific requirements of serious game design for interactive history and digital heritage.